KEHADIRAN KRISTIANI DALAM POLITIK: REKONSTRUKSI TEOLOGI MISI TENTANG PERAN KEKRISTENAN DALAM RUANG PUBLIK POLITIS DI INDONESIA - Grets Janialdi Apner Siregar (Bethel Press, 2021)
This article offers a theological reconstruction of church presence in political public sphere as an evangelism. I use sociological-historical criticism that makes up for a missiological perspective on public sphere as a basis for critique of the model of religious presence in the political public sphere in Indonesia. The followed by the evangelism theory as a peaceful and undominant Christian presence in public sphere. It is to prove that the church, through the people, can and will need to take an active role I political public sphere as and evangelism in politics.